Umbilical artery thrombosis and maternal positive autoimmune antibodies: two case reports and a literature review - Li, Xin; Chen, Wei; Liu, Tianjiao; Cai, Jian; Wei, Sumei; Du, Yuhua; Liu, Chunyan; Gong, Zhaolin; Cheng, Linbo; Zhou, Xiaoling; Xiong, Min; Wang, Tao; et al. (Frontiers in Medicine, 2023)
Background Previous studies have shown that abnormal increases in autoimmune antibodies in pregnant women may increase the risk of maternal thrombosis. However, at our hospital, two pregnant women presented with umbilical artery thrombosis and positive maternal autoantibodies were detected in both, which led us to consider whether maternal autoantibodies also played a role in umbilical artery thrombosis. Case presentation Case 1: Fetal ultrasound of a 34-year-old pregnant woman at 30+4 weeks gestation showed two umbilical arteries, with an inner diameter of approximately 0.15 cm for the smaller was artery. However, only a single umbilical artery blood flow signal was detected. Due to fetal distress, which was noted on abnormal cardiotocography and Doppler ultrasound, an emergency cesarean section was performed at 31+1 weeks gestation. The Apgar score of the newborn was 3-8-8. Umbilical cord examination detected thrombosis in the two umbilical arteries. Moreover, blood test results during pregnancy showed nRNP/Sm antibody (+) and SS antibody (+++). Case 2: The first systematic ultrasound of a 33-year-old twin pregnancy at 24+3 weeks gestation was normal, but routine fetal ultrasound at 27+1 weeks gestation showed only one umbilical artery between fetus A and the placenta. Blood test results showed that the patient was anti-nRNP/Sm antibody (+) in the rheumatoid immune activity test at 27+3 weeks gestation. An emergency cesarean section was performed at 34+6 weeks gestation because of the single umbilical artery and abnormal maternal coagulation. Both umbilical cords of fetus A and B blood test results showed anti-nRNP/Sm antibody (++). The pathological examination of the umbilical cord and placenta showed the presence of old thrombosis in one of the umbilical arteries of fetus A. Conclusions Abnormal maternal autoantibodies may be a risk factor for umbilical artery thrombosis. For these pregnant women, conducting more detailed ultrasound monitoring might get early detection of UAT formation and avoid the occurrence of adverse pregnancy outcomes.